2018
DOI: 10.1111/jfbc.12600
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antibacterial properties of guava leaf extracts as affected by solvents used for prior dechlorophyllization

Abstract: The impacts of different solvents used for removing chlorophyll in guava leaf powder on antioxidant and antibacterial properties of resulting ethanolic extracts were studied. Among all solvents, acetone was the most effective in chlorophyll removal, followed by chloroform as indicated by the lowest chlorophyll a and b contents in resulting extract. However, the ethanolic extract from leaf powder dechlorophyllized using acetone (ACE) showed the lowest antioxidant activities, except for H2O2 scavenging activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(95 citation statements)
references
References 35 publications
4
91
0
Order By: Relevance
“…Drying, grinding, or size reduction of the plant materials and, sometimes, dechlorophyllization, depending on the plant material, are the major processes in the pre-extraction stage (Azwanida, 2015;Chotphruethipong, Benjakul, & Kijroongrojana, 2017). Olatunde, Benjakul, and Kitiya (2018) demonstrated that solvents have a profound role in dechlorophyllization of guava leaf, in which the ethanolic extract from chloroform-dechlorophyllized leaf powder showed the highest antioxidant efficacy. However, the extract of leaves dechlorophyllized with acetone had very low yield.…”
Section: Preparation and Extraction Of Plant Extracts And Essential Oilsmentioning
confidence: 99%
“…Drying, grinding, or size reduction of the plant materials and, sometimes, dechlorophyllization, depending on the plant material, are the major processes in the pre-extraction stage (Azwanida, 2015;Chotphruethipong, Benjakul, & Kijroongrojana, 2017). Olatunde, Benjakul, and Kitiya (2018) demonstrated that solvents have a profound role in dechlorophyllization of guava leaf, in which the ethanolic extract from chloroform-dechlorophyllized leaf powder showed the highest antioxidant efficacy. However, the extract of leaves dechlorophyllized with acetone had very low yield.…”
Section: Preparation and Extraction Of Plant Extracts And Essential Oilsmentioning
confidence: 99%
“…However, these processes are not entirely selective and can result in a reduction in the levels of the compounds with technological capacities in the decolorized extracts (Berdahl & McKeague, ). Different organic solvents (acetone, methanol, propanol, and chloroform) have also been assessed for eliminating chlorophyll from ethanolic extracts of guava leaf powder (Olatunde, Benjakul, & Vongkamjan, ). This study showed that nonpolar solvents such as chloroform were suitable for chlorophyll removal and maintained the antioxidant and antibacterial potentials of the extracts, while polar solvents (methanol, propanol, and acetone) resulted in reduction of both the antioxidant and antimicrobial activities (Olatunde et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Different organic solvents (acetone, methanol, propanol, and chloroform) have also been assessed for eliminating chlorophyll from ethanolic extracts of guava leaf powder (Olatunde, Benjakul, & Vongkamjan, ). This study showed that nonpolar solvents such as chloroform were suitable for chlorophyll removal and maintained the antioxidant and antibacterial potentials of the extracts, while polar solvents (methanol, propanol, and acetone) resulted in reduction of both the antioxidant and antimicrobial activities (Olatunde et al, ). Hence, decolorization constitutes a significant potential hurdle in the production and the subsequent applicability of plant extracts from herbs and their by‐products in food formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al (2016) and Lu, Patil, Keener, Cullen, and Bourke (2014) documented that the mode of bacterial inactivation by plasma generated using atmospheric air varied with the type of bacteria. GPB are more resilient to antimicrobial agent treatment, which is attributed to their cell wall containing several layers of peptidoglycan in comparison with GNB with single layer of peptidoglycan and several layers of lipopolysaccharide (Olatunde, Benjakul, & Vongkamjan, 2018, 2019c.…”
Section: Introductionmentioning
confidence: 99%